Carbon nanoarch encapsulating Fe nanowire on NI(111) - David, Melanie Y. (Animo Repository, 2006)
We investigate the stable structures of single-walled carbon nanotubes (SWNTs) on Ni(111) and when a SWNT is filled with Fe wire on Ni(111), based on density functional theory. We find stable geometries and electronic states for the nanotube on Ni(111). We propose the possibility that the C–C bonds of a carbon nanotube are broken by an Fe wire and a Ni surface. That is, when an Fe-filled SWNT (3,3) adsorbs on Ni(111) surface, the SWNT transforms into an arch-like structure.